2020
DOI: 10.1021/acsnano.9b06837
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Seeding Nanocavities: Multiple Polymer Foam Cell Nucleation by Polydimethylsiloxane-Grafted Designer Silica Nanoparticles

Abstract: We describe a successful strategy to substantially enhance cell nucleation efficiency in polymer foams by using designer nanoparticles as nucleating agents. Bare and poly­(dimethylsilane) (PDMS)-grafted raspberry-like silica nanoparticles with diameters ranging from ∼80 nm to ∼200 nm were synthesized and utilized as highly efficient cell nucleators in CO2-blown nanocellular polymethyl methacrylate (PMMA) foams. The successful synthesis of core–shell nanoparticles was confirmed by Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…In principle, there are no physical restrictions that prevent the occurrence of more than one nucleation event per particle, that is, nucleation efficiencies exceeding unity are possible. 46 …”
Section: Resultsmentioning
confidence: 99%
“…In principle, there are no physical restrictions that prevent the occurrence of more than one nucleation event per particle, that is, nucleation efficiencies exceeding unity are possible. 46 …”
Section: Resultsmentioning
confidence: 99%
“…The presence of the micelle cores almost perfectly centered in the cells (Figures 7 and S2, see Supplementary Materials), and the proposed energetic preference of nucleation to happen directly inside the PBA phase (i.e., decreasing the energy barrier due to the lower Gibbs energy of the PBA phase and avoiding the contribution of the line tension) [23,28], suggest that the cell nucleation happens simultaneously at several points of the PBA shell (Figure 8a,b). Moreover, the remaining structures or filaments between the micelle cores and the cell walls could be considered evidence of multiple nucleation sites, as proposed in the work of Liu et al [44]. Another nucleation process, such as a single nucleation point or nucleation in the interfaces, would probably displace the micelle cores from the center.…”
Section: Cell Nucleation In the Near-equilibrium Nanostructuration Of Pmma/mam Blendsmentioning
confidence: 91%
“…In the last years, several studies were conducted focusing on the effect of nucleating species in the fabrication of nanocellular polymers, such as nanoparticles [ 17 , 18 , 19 , 20 ] or an immiscible polymeric second phase [ 21 , 22 ]. For instance, Liu et al [ 23 ] synthesize silica nanoparticles with different surface roughness to enhance the nucleation of poly(methyl-methacrylate) PMMA. They employed the same quantity of silica nanoparticles on each compound (around 10 13 particles/cm 3 ) and observed that increasing the surface roughness promotes a higher nucleation density because the energy barrier which promotes the cell nucleation is lower for concave surfaces than for flat-convex surfaces [ 24 ].…”
Section: Introductionmentioning
confidence: 99%